"It's about hearing and understanding their stories": Teacher empathy and socio-political awareness toward newcomer undocumented students in the New Latino South. Issue 2 (2nd April 2020) - Rodriguez, Sophia; Monreal, Timothy; Howard, Joy
ABSTRACT: In this article the co-authors draw from three separate ethnographic studies in the U.S. South to expand the literature about how teachers understand and apply multiculturalism specifically when working with newcomer undocumented immigrant youth. The co-authors identify an implementation gap between what is known about critical multicultural education and how it is put into practice by educators, specifically in regions that can be characterized as constrained policy contexts. Findings from collective analyses of data across all three studies add to multicultural education literature by directly addressing the ways in which policies govern the everyday lives of newcomers and inform the practices of their teachers. Key findings that represent generative dispositions and practices among teachers of newcomer students were strategic teacher empathy and sociopolitical awareness. The article concludes with a discussion of implications for practice and future research.